THE IMPORTANCE OF MEN’S HEALTH CARE (Годишен зборник на Филозофски факултет - Скопје, 2023)
It is evident, backed by research that men tend to avoid medical examinations much more frequently than women. Statistics show that women are more likely to visit medical professionals for preventive measures, health consultations, and examinations, with a probability of over 95%. Surprisingly, despite women having a significantly higher life expectancy, men need to recognize the importance of preventive health examinations. Timely consultations with healthcare providers can effectively prevent various diseases, including those with fatal consequences. Fortunately, many of these conditions can be prevented and treated. To achieve this, it is crucial to launch more proactive campaigns aimed at raising awareness among men on these critical topics.This paper analyses the status of men’s health and provides available data. Additionally, through a quantitative research study, it aims to provide a comprehensive understanding of the situation in the Republic of North Macedonia.The goal is to emphasize the significance of men’s health care, encourage regular medical check-ups, and promote a proactive approach to preventive measures. By doing so, we can ensure better health outcomes for men and contribute to a healthier society overall.